QUALITY OF AIR BACTERIA IN OPERATING THEATER IN SOME HOSPITALS IN JAKARTA AND SURROUNDINGS AREAS IN 2018-2019 - CONNY RIANA TJAMPAKASARI; NABILA NAURA; TJAHJANI MIRAWATI SUDIRO (Indonesian Society for microbiology, 2020)
Nosocomial infection is an infection obtained by a patient or hospital staff while in hospital. This infectionplays a role in causing morbidity and mortality in hospitals and can occur in various hospitals rooms, includingoperating theaters. Nosocomial infections can occur due to various factors, one of which is contamination fromairborne bacteria. In some countries, regulations are set to limit the concentration of airborne bacteria, both in theoperating theaters and other rooms in hospitals, hence the need for monitoring and supervision of air quality asareflection on the cleanliness conditions in hospitals. Based on this, it is necessary to know the bacteriological airquality in the operating theaters in several hospitals in Jakarta and surrounding areas as one of the steps to preventnosocomial infections. The method uses an air sampler with the principle of impaction. Air sampler works byseparating the particles from the air by utilizing the inertia of the particles to force the bacteria to settle to thesurface of the medium. A total of 217 examinations in the operating theaters were carried out in 17 hospitals inJakarta and surrounding areas during January 2018 to June 2019. The majority of the operating theaters inhospitals in Jakarta and surrounding areas have air quality that met appropriate quality standards. In 2018, 120 of137 (87.59%) examination in the operating theaters met the quality standar. Meanwhile in 2019, 70 of 80(87.50%) operating theaters met the standard determined by the Ministry of Health of the Republic of Indonesia. Key words: air sampler method, operating theater, quality of air bacteria